Hipernatremia em uma unidade de terapia intensiva pediátrica - Eliseu, Tatiana Lelis de Faria (2019)
Introduction: Dysnatremias are the electrolyte disturbances most frequently observed in clinical practice. The general prevalence of hypernatremia in adult Intensive Care Units is 9% to 14.3% and its occurrence is related to a significant increase in morbidity and mortality. Few studies address the epidemiology of hypernatremia in the pediatric population. Objectives: Verify the prevalence of hypernatremia and to characterize its relationships with demographic, clinical and evolutionary variables in a Pediatric Intensive Care Unit (PICU). Methods: Retrospective cohort performed at a PICU of a university hospital between January 2005 and December 2015. The patients were divided in the following groups: without dysnatremia, sodium ≥ 135 mEq/L and ≤ 145 mEq/L, hyponatremia, sodium < 135 mEq/L, and hypernatremia, sodium > 145 mEq/L. Patients with hypernatremia were classified according to severity and timing of detection and compared to those without dysnatremia according to demographic variables (sex and age), clinical variables (main diagnosis of admission and Pediatric Risk of Mortality - PRISM) and evolutionary variables (PICU length of stay, time of invasive mechanical ventilation and mortality). Results: Of the 2145 admissions analyzed, 299 (13.9%) presented hypernatremia. Patients with hypernatremia presented a higher frequency of complex chronic disease (91.7%, p = 0.000), higher PRISM (mean = 15.2 / SD = 10.6, p = 0.000), longer PICU length of stay (mean = 16,6 days / SD = 33,4; p = 0,000), longer time of invasive mechanical ventilation (mean = 9.4 days / SD = 16.3, p = 0.000) and higher mortality (22.1%, p = 0.000). The main diagnoses observed in these patients were postoperative cardiac surgery (33.8%), sepsis (14.7%) and diffuse brain distress (13%). There was a predominance of mild hypernatremia (72.6%) and hypernatremia on admission (64%). Conclusions: Hypernatremia is relatively frequent in the PICU and is identified primarily on admission. Besides that, it had an impact on morbidity and was an independent risk factor for mortality.